4T1 Mammary Carcinoma Colonization of Metastatic Niches Is Accelerated by Obesity - Evangelista, Gabriela Coeli Menezes; Salvador, Pollyanna Amaral; Soares, Sara Malaguti Andrade; Barros, Luciana Rodrigues Carvalho; Xavier, Felipe Henrique da Cunha; Abdo, Luiza Macedo; Gualberto, Ana Cristina Moura; Macedo, Gilson Costa; Clavijo-Salomon, Maria Alejandra; Gameiro, Jacy (Frontiers in Oncology, 2019)
Breast cancer (BC) remains the leading cause of cancer-related deaths among women, and the chances to develop it are duplicated by obesity. Still, the impact of obesity during BC progression remains less understood. We investigated the role of obesity in tumor progression using the murine model of 4T1 mammary carcinoma in BALB/c female mice, previously high-fat-diet (HFD) fed. HFD induced obesity, metabolic impairment, and high serum and fat leptin levels. After injection of 4T1-cells, HFD-mice accelerated tumor progression and metastasis. 4T1-cells found within HFD-mice metastatic niches presented higher clonogenic potential. 4T1-cells treated in vitro with fat-conditioned medium derived from HFD-mice, increased migration capacity through CXCL12 and CCL25 gradients. In HFD-mice, the infiltration and activation of immune cells into tumor-sentinel lymph nodes was overall reduced, except for activated CD4+ T cells expressing low CD25 levels. Within the bone marrow, the levels of haematopoiesis-related IL-6 and TNF-α decreased after 4T1-cells injection in HFD-mice whereas increased in the controls, suggesting that upregulation of both cytokines, regardless of the tumor, is disrupted by obesity. Finally, the expression of genes for leptin, CXCR4, and CCR9 (receptors of CXCL12 and CCL25, respectively) was negatively correlated with the infiltration of CD8 T cells in human triple-negative BC tumors from obese patients compared to non-obese. Together, our data present early evidence of systemic networks triggered by obesity that promote BC progression to the metastatic niches. Targeting these pathways might be useful to prevent the rapid BC progression observed among obese patients.